2017
DOI: 10.21873/anticanres.12155
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma of the Vagina: Case Report and Systematic Review of the Literature

Abstract: Abstract. Background: Primary melanoma of the vagina (PMV) is a rare entity. The prognosis of women with PMV is poor and there is no standardized therapy for this type of malignancy. We present the case of a 72-year-old womanwith PMV (cT2, pN0, M0 Melanoma is caused by the malignant transformation of pigment cells. Apart from the skin, pigment cells such as melanocytes are present in various mucosal linings such as those of the gastrointestinal, respiratory, and urogenital tracts (1). Thus, in addition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Surgery, combined with adjuvant radiotherapy, chemotherapy and immunotherapy (interferon alpha) have been discussed as other modes of treatment [8]. Since the patient is physically weak and at the extreme of age, she was not offered adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, combined with adjuvant radiotherapy, chemotherapy and immunotherapy (interferon alpha) have been discussed as other modes of treatment [8]. Since the patient is physically weak and at the extreme of age, she was not offered adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 51 In a 2017 systematic review of 805 cases reported over the last 20 years (mostly case reports), the mean recurrence‐free survival was short, at 16 months, with a mean overall survival of only 22 months. 52 …”
Section: Prognoses and Outcomes Of Vaginal Cancermentioning
confidence: 99%
“…Hence, the skin is the most common site of melanoma, with cutaneous melanoma (CM) being the 19th most common cancer worldwide [ 3 ]. The vagina is a rare site for the origin of mucosal melanoma (MM) and accounts for only 0.3%-0.8% and, in some studies, up to 1.4% of all melanomas [ 4 , 5 ]. MMs are considerably more common in women than in men.…”
Section: Introductionmentioning
confidence: 99%
“…MMs are considerably more common in women than in men. Primary vaginal malignant melanoma (PVMM) usually develops in the lower third and is mostly present as either inconsistently pigmented grey or black nodular, fungating or polypoid soft mass ranging from 0.5 to 0.8 cm in size in the anterior wall of the vagina [ 5 , 6 ]. Most patients with PVMM present with irregular vaginal bleeding or increased discharge from the vagina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation